2000
DOI: 10.1016/s0035-9203(00)90455-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the immunological surveillance value of humoral and lymphocyte assays in severe human cystic echinococcosis

Abstract: Thirty cystic echinococcosis (CE) patients in Uruguay with severe bone or secondary disseminated echinococcosis were immunologically assessed using cellular (lymphocyte transformation assay, LTA) and humoral (specific antibody and subclass responses, circulating antigen and circulating immune-complexes) immunological assays during the course of chemotherapy (albendazole and/or praziquantel). CE patients were divided into 4 groups, according to clinical treatment and outcome: (I) surgery and chemotherapy, (II) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…They also support the role of HFF in eliciting a preferentially Th1 activation [29]. Our data on IgG4 again support the reported closer association of the specific IgG4 isotype with nonresponding patients than with those who respond well [5,33,34].…”
Section: Discussionsupporting
confidence: 87%
“…They also support the role of HFF in eliciting a preferentially Th1 activation [29]. Our data on IgG4 again support the reported closer association of the specific IgG4 isotype with nonresponding patients than with those who respond well [5,33,34].…”
Section: Discussionsupporting
confidence: 87%
“…However, seronegativity may develop because unknown host and/or parasite factors cause inadequate T-helper-2 cell activation, thus reducing production of T-helper-2 cytokines implicated in immunoglobulin expression in cystic echinococcosis (Rigano et al 1998). Bonifacino et al (2000) found increased circulating antigen and speci c antibodies, especially total speci c immunoglobulin, of prognostic value in some patients with severe bone or secondary disseminated echinococcosis where the levels remained high and/or increased. However, while the level of total IgE decreased in our patient no.…”
Section: Discussionmentioning
confidence: 99%
“…This response in our series may have been due to albendazole/ mebendazole treatment. Indeed, Bonifacino et al (2000) found that antigen-speci c in vitro lymphocyte transformation assays show a signi cantly lower response than controls during albendazole treatment, but return to normal levels in healed patients due to parasite-induced suppress ion of cellular responses.…”
Section: Discussionmentioning
confidence: 99%
“… 20 Bonifacino et al looked at patients with secondary disseminated hydatid disease or with severe bone involvement and concluded that the role of praziquantel use in these severe cases required further appraise. 20 , 21 Although it has been suggested that praziquantel used in combination with albendazole may have synergistic effects resulting in increased levels of albendazole, 19 , 22 there is limited evidence on whether this dual therapy is superior compared with albendazole alone. 20 Gdoura et al 3 described a protocol with albendazole administered at a dose of 400 mg, orally, twice daily 2 weeks before surgery and approximately 6 months postsurgery.…”
Section: Discussionmentioning
confidence: 99%